2014
DOI: 10.1007/s00395-014-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cardioprotective mechanisms of immediate, early and delayed ischaemic postconditioning

Abstract: Cardioprotection against ischaemia/reperfusion injury in mice can be achieved by delayed ischaemic postconditioning (IPost) applied as late as 30 min after the onset of reperfusion. We determined the efficacy of delayed IPost in a rat model of myocardial infarction (MI) and investigated potential underlying mechanisms of this phenomenon. Rats were subjected to 20, 30 or 45 min of coronary artery occlusion followed by 120 min of reperfusion (I/R). Immediate and early IPost included six cycles of I/R (10/10 s) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
4
14
0
Order By: Relevance
“…However, Lambert et al (2014) demonstrated that in diabetic rats NaSH-induced postconditioning might signal through the other arm of the RISK pathway, namely ERK1/2. LY294002 alone had no significant effect on either the infarct size or Akt phosphorylation compared to control which is consistent with the findings of other investigators , Barsukevich et al, 2015.…”
Section: Gyy4137 Postconditioning Activates Pi3k/akt Signallingsupporting
confidence: 92%
“…However, Lambert et al (2014) demonstrated that in diabetic rats NaSH-induced postconditioning might signal through the other arm of the RISK pathway, namely ERK1/2. LY294002 alone had no significant effect on either the infarct size or Akt phosphorylation compared to control which is consistent with the findings of other investigators , Barsukevich et al, 2015.…”
Section: Gyy4137 Postconditioning Activates Pi3k/akt Signallingsupporting
confidence: 92%
“…However, delayed LPR (from 10 minutes) did not preserve PI3K activation ( Figure E1, A and B). This last observation was confirmed in the study by Barsukevich and colleagues,5 in which delayed postconditioning did not induce phosphorylation of Akt, Erk ½, and Stat. Thus, it can be suggested that distinct cardioprotective mechanisms seem to be involved between early postconditioning-LPR (which implies Akt-P and Erk-P) and late LPR.…”
Section: Mechanism Of Action Of Low-pressure Reperfusionsupporting
confidence: 59%
“…[1][2][3] This very narrow therapeutic time window may limit postconditioning application in the clinical setting. Two recent studies proposed that the protective effect of ischemic postconditioning may persist even when applied several minutes after reflow in the in vivo mouse 4 and rat 5 models, but the mechanism of protection remains to be determined. By invalidation of the prevailing concept, these new studies open a new way for cardioprotection.…”
Section: Perspectivementioning
confidence: 97%
See 1 more Smart Citation
“…Identification of robust cardioprotective reperfusion strategies has been the subject of intense research activity for several years, but promising pre-clinical approaches have seldom provided convincing cardioprotection in patients with ST-segment elevation myocardial infarction (STEMI) (Downey and Cohen, 2009; Lloyd-Jones, 2010; Kloner, 2013; Bulluck et al, 2016). This might be explained by interfering effects of co-morbidities and/or concomitant therapies (Hausenloy and Yellon, 2004; Bell and Yellon, 2012), delayed application of cardioprotective strategies (Roubille et al, 2014) and/or too long or too short ischemia (Barsukevich et al, 2015). However, with DCD cardiac grafts, donors will be subject to donor selection, and thus patients will generally be young and healthy, thereby limiting possible negative effects associated with comorbidities and medical therapies.…”
Section: Introductionmentioning
confidence: 99%